2012
DOI: 10.1016/j.radphyschem.2011.11.043
|View full text |Cite
|
Sign up to set email alerts
|

E-beam crosslinked, biocompatible functional hydrogels incorporating polyaniline nanoparticles

Abstract: a b s t r a c t PANI aqueous nanocolloids in their acid-doped, inherently conductive form were synthesised by means of suitable water soluble polymers used as stabilisers. In particular, poly(vinyl alcohol) (PVA) or chitosan (CT) was used to stabilise PANI nanoparticles, thus preventing PANI precipitation during synthesis and upon storage. Subsequently, e-beam irradiation of the PANI dispersions has been performed with a 12 MeV Linac accelerator. PVA-PANI nanocolloid has been transformed into a PVA-PANI hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The presence of PAG just slightly reduced the cell viability during the test period, therefore, it can be concluded that the optimum scaffolds with PAG have supported the proliferation of MSCs during the test period. Non-toxicity of polyaniline against cells has been previously reported in other studies; Dispenza et al 33 evaluated cell viability of human dermal fibroblast cells on 4, 48, and 72 h after incubation on polyvinyl alcohol (PVA) and PVA/PANI hydrogels and reported there was not any cytotoxic activity on the samples with polyaniline. Liu et al 34 investigated cell biocompatibility of polyaniline film using PC-12 cells and concluded its ability for cell proliferation and its potential to cultivate neuronal cells for applications in tissue engineering.…”
Section: Characterization Of Optimum Scaffoldmentioning
confidence: 67%
“…The presence of PAG just slightly reduced the cell viability during the test period, therefore, it can be concluded that the optimum scaffolds with PAG have supported the proliferation of MSCs during the test period. Non-toxicity of polyaniline against cells has been previously reported in other studies; Dispenza et al 33 evaluated cell viability of human dermal fibroblast cells on 4, 48, and 72 h after incubation on polyvinyl alcohol (PVA) and PVA/PANI hydrogels and reported there was not any cytotoxic activity on the samples with polyaniline. Liu et al 34 investigated cell biocompatibility of polyaniline film using PC-12 cells and concluded its ability for cell proliferation and its potential to cultivate neuronal cells for applications in tissue engineering.…”
Section: Characterization Of Optimum Scaffoldmentioning
confidence: 67%
“…Each component of the cryogel–CP composites has attracted tremendous attention in research and technological applications because of their superporosity, elasticity, flexibility, high mechanical strength, fast responsiveness, and electronically active and conducting nature of p(An) . The lone electron pairs on nitrogen participate in conjugation, and the doping is associated with a chain protonation mechanism in p(An) that leads to electronic conductions.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the relatively good electrical conductivity and high chemical and thermal stability, p(An)‐based conducting polymers could be used in electronic devices, actuators, and sensors. P(An) can undergo reversible acid–base doping–dedoping behavior because of its readily controllable properties, including its free volume, solubility, optical activity, and electrical conductivity . Interestingly, polyelectrolyte hydrogels, such as poly(2‐acrylamido‐2‐methyl‐1‐propane sulfonic acid sodium salt) [p(AMPS)], poly(3‐acrylamidopropyltrimethyl ammonium chloride) [p(APTMACl)], and poly(acrylic acid) [p(AAc)], also provide ionic conductivity because of their ionic‐group‐developing functional groups .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, PANI nanoparticles formed with the steric stabilizers poly(vinyl alcohol) (PVA) or CT were used to make nanostructured PANI-PVA hydrogels by crosslinking the PVA in the dispersion via E-beam irradiation. 66 The hydrogels were demonstrated to be non-cytotoxic with excellent cell viability of human dermal fibroblasts after 72 h.…”
mentioning
confidence: 99%